The market of full-cycle construction companies: analysis of the current state and key trends - Yu. A. Laamarti; E. G. Dedov; A. A. Nikolaev (Vestnik MGSU, 2024)
Introduction. In the present-day environment, development of the market of full-cycle construction companies needs a thorough research on key trends governing its operation and improvement. Due to the gradual digitalization of the construction industry, traditional approaches to its analysis, based on geographical and product boundaries in terms of the number, the floor area and the volume of constructed buildings, will become ineffective because they disregard alternative criteria characterizing digital construction markets. Against this background, the projected development of the market of full-cycle construction companies is misleading. The evolution of methods for analyzing the market of full-cycle construction companies is characterized by a shift towards the use of digital ecosystems by developers willing to interact with market players. Hence, big data and data access modes will become increasingly important in the construction industry. The purpose of the study is to analyze the current state and trends in the Russian market of full-cycle construction companies.Materials and methods. Theoretical analysis of research works, statistical data analysis and comparative analysis, data generalization and systematization are among the main research methods.Results. Key trends governing the development of the market of full-cycle construction companies were identified by means of secondary data processing and computing the average annual growth rate. The main factors determining the current state of the market of full-cycle construction companies were systematized. Opinions of scientists, experts, as well as statistics were analyzed to systematize the reasons and factors, characterizing the current state of this market.Conclusions. Despite the positive dynamics, observed in the market of full-cycle construction companies, some administrative and legal factors restrain its development and act as barriers to its qualitative changes. In turn, regulatory authorities must meet the challenge of introducing digital technologies in the construction industry amid sanctions and import substitution of software for full-cycle construction companies preferring foreign alternatives.